UTHM Muslim Students Proficiency on the Ahl Sunnah Wal Jamaah Background, Characteristics and Aqeedah Methodologies - et. al., Shakila Ahmad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ahl Sunnah Wal Jamaah (ASWJ) is a name given to a dominant group of Muslims who adhere to the teaching brought by Rasullah SAW and his companions. In Malaysia, ASWJ Asyai’rah has its place in the main stream and is being used in Islamic education modules at all levels of studies starting from pre-school up to secondary school. As a result it has been able to create uniformity and harmony in Muslim students way of thought when they are at tertiary level. It is expected that all Muslim students undergo a formal education process about ASWJ background, characteristics and methodologies that are used in aqeedah discussion. The article is intended to explain a research pertaining to Universiti Tun Hussein Onn Malaysia muslim students proficiency towards ASWJ background, characteristics and methodologies used in discussing aqeedah. A total of 236 diploma students were involved in the study. At the time of the study, the students were undertaking Introduction of Islamic Studies (UQI10402) course that was offerred by the Department of Islamic Studies, Centre for General Studies and Co-curriculum during a special semester. Students were required to respond to 20 items serving as indicators on ASWJ background, characteristics and methodologies. 5 points likert scales were employed in the Google Form survey. The findings indicates a very high level of students proficiency on the ASWJ backgrounds and characteristics (mean=4.620). However, upon anlysis there are four items in methodologies indicating a high level of proficiency(mean=3.915 to 4.169). The findings is hoped to give valuable information to the related authorities in strengthening the ASWJ aqeedah module namely; UTHM Islamic Centre, Ahl Sunnah Wal Jamaah Institute,UTHM, UTHM General Studies and Johor Islamic Council.